Dysregulation of club cell biology in idiopathic pulmonary fibrosis. - Wu-Lin Zuo; Mahboubeh R Rostami; Michelle LeBlanc; Robert J Kaner; Sarah L O'Beirne; Jason G Mezey; Philip L Leopold; Karsten Quast; Sudha Visvanathan; Jay S Fine; Matthew J Thomas; Ronald G Crystal (PLoS ONE, 2020)
Idiopathic pulmonary fibrosis (IPF) is a progressive, chronic fibrotic lung disease with an irreversible decline of lung function. "Bronchiolization", characterized by ectopic appearance of airway epithelial cells in the alveolar regions, is one of the characteristic features in the IPF lung. Based on the knowledge that club cells are the major epithelial secretory cells in human small airways, and their major secretory product uteroglobin (SCGB1A1) is significantly increased in both serum and epithelial lining fluid of IPF lung, we hypothesize that human airway club cells contribute to the pathogenesis of IPF. By assessing the transcriptomes of the single cells from human lung of control donors and IPF patients, we identified two SCGB1A1+ club cell subpopulations, highly expressing MUC5B, a significant genetic risk factor strongly associated with IPF, and SCGB3A2, a marker heterogeneously expressed in the club cells, respectively. Interestingly, the cellular proportion of SCGB1A1+MUC5B+ club cells was significantly increased in IPF patients, and this club cell subpopulation highly expressed genes related to mucous production and immune cell chemotaxis. In contrast, though the cellular proportion did not change, the molecular phenotype of the SCGB1A1+SCGB3A2high club cell subpopulation was significantly altered in IPF lung, with increased expression of mucins, cytokine and extracellular matrix genes. The single cell transcriptomic analysis reveals the cellular and molecular heterogeneity of club cells, and provide novel insights into the biological functions of club cells in the pathogenesis of IPF.